(untitled) (Materiali di Estetica. Terza serie, 2017)
The essay is an investigation into the relationship between the structure of the crime novel and philosophy. Three structural approaches are presented by Bertold Brecht, Walter Benjamin and Ernst Bloch. They relate to the anthropological and social function of the crime novel. The inner form of the detective novel is an effective means of aesthetics and understanding the complexity of our contemporary reality by simplifying it. At the end, these functions are illustrated using a current example in German society.